Patients’ Characteristics and Initial Therapy at Diabetic Center of Sanglah General Hospital in 2018 - Tjokorda Gde Agung Senapathi (Journal of Global Pharma Technology, 2016)
Background: Diabetes mellitus (DM) is a chronic disease that requires medical treatment and education to prevent acute or chronic complications. Until today, there have been no published records in the incidence of DM in Bali. The goal of this study was to observe the characteristics of patients who visited Diabetic Center of Sanglah General Hospital in 2018. Methods: This was a cross-sectional, retrospective study. The subjects of this study were all patients newly-diagnosed with DM, aged 18 or older, who came to the Diabetic Center of Sanglah General Hospital. The sampling method was all-inclusive sampling. We recorded the age, sex, body height, body weight, body mass index (IMT), baseline fasting blood sugar, and baseline HbA1C. The data were analyzed descriptively. Results: In 2018, 1,145 patients visited the Diabetic Center of Sanglah General Hospital. The majority of the subjects were men (66.11%), with the most frequent age-group was the 50-69 years age group (69.08%). As many as 117 patients received OADs as initial therapy, while 840 received insulin, and the remaining 665 received a combination of both OAD and insulin. Conclusions: There were 1,145 patients visited the Diabetic Center of Sanglah Hospital in 2018, with the highest age-group was the 50-69 years age group. Only a small number of them received OADs as initial therapy, and most of received the combination of insulin and OADs.Keywords: Diabetes mellitus, Age, Sex, Bali, Indonesia.